Effect of elevated temperature and cooling regimes on the compressive strength, microstructure and radiation attenuation of fly ash–cement composites modified with miscellaneous nanoparticles. (20th October 2020) - Selim, F.A.; Amin, M.S.; Ramadan, M.; Hazem, M.M.
Highlights: Effect of nanoparticles incorporation on 28-days compressive strength of OPC-20FA composite was examined. Effect of elevated temperature on the mechanical characteristics and pore structure parameters was investigated. Radiation shielding for OPC-20FA-NPs at 250 °C was studied. Various hydrates with different morphologies were identified at elevated temperatures. Abstract: This study aims to investigate the consequence of elevated temperature on the compressive strength, microstructure and γ-radiation mitigation of OPC/fly ash (FA) composites modified with different doses of carbon nano tubes (CNTs), nano meta -kaolin (NMK), nano-Fe2 O3 (NFO) and nano-NiO (NNO). Four different contents of CNTs were applied: 0.05, 0.1, 0.15, 0.2 wt% whereas, the contents for the other selected NPs were: 0.25, 0.5, 1, 2%. All blends were prepared utilizing constant water/solid (W/S) ratio of 0.27 with the aid of poly carboxylate superplasticizer. After 28 days of hydration, all specimens were heated at 250, 500 and 750 °C for 3 h. The fired composites were cooled by two various regimes (gradual in air & rapid in tap water). Residual strength, total porosity, phase composition, microstructure and γ-radiation shielding were examined. OPC-fly ash blends accommodating 0.1, 1, 0.5 and 0.5% of CNTs, NMK, NFO and NiO NPs, respectively exhibited the best performance of fire resistivity and γ-radiation shielding. Evidently, the composite containing 0.5 NFO possessed the best fire resistivity and γ-radiation shielding among other mixes and the order of NPs performance was 0.5 NFO > 0.1CNTs > 1NMK > 0.5NNO. XRD and DTA analyses emphasized the development of various phases at elevated temperatures (CSHs, CASHs, CAHs, CFHs, CFSHs, AFm, AFt, andradite, rankinite, gismondine, akermanite and wollastonite). Moreover, SEM images affirmed high compactions for most composites at 250 °C and high porosity at 750 °C.